(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
In this text I focus on the artivist corpographies of feminist artists who use bodies in a constitutive, that is, performative way, to undermine the presuppositions of traditional representation starting from a critique of the notion of species. Their actions interfere with the fetishism of representation, based on the distance of the beholder from the object of observation, and inaugurate a space of implication in which none of the subjects involved, including nonhuman animals, occupy a given position before the performative event. These artists move on both an aesthetic and social level, deliberately appealing to indeterminacy as a political resource, so that every emerging subjectivity in performative actions exercises its own capacity for action and response.